The Forms of the Urban and Natural Environmens in the Proses of Márius Kopcsay, Monika Kompaníková and Peter Krištúfek - Katarína Badžgoňová (Slovenska Literatura, 2020)
The paper deals with the relation between the urban and natural/rural environments in contemporary Slovak prose with regard to Slovak literary tradition and reflecting on the current changes of a town as exemplified by texts of three authors M. Kopcsay, M.Kompaník andP. Krištúfek. Slovak literature was dominated by the anti-urban solution to the antinomy of the urban and natural environments – the negative depiction of a town along with idealization of the natural environment, which are still in use. The texts reflect on the transformations of a contemporary town and show that the ideal of natural life is an urban construct to a certain extent, and they challenge the traditional motif of a journey from a town back to the country and thematize the disappearing boundaries between the urban and natural environments by using the motifs of the uncontrolably expanding urban environment, peri-urbanization as well as the motifs of urban wilderness. At the same time, by blending foreign elements the texts employ heterogeneity and ambiguity typical of the urban environment.